Post-operative delirium in the patient with hip fracture: The journey from hospital arrival to discharge - Ní Chróinín, Danielle; Chuan, Alwin (Frontiers in Medicine, 2022)
Delirium- an acute disorder of attention and cognition- is the commonest complication following hip fracture. Patients with hip fracture are particularly vulnerable to delirium, and many of the lessons from the care of the patient with hip fracture will extend to other surgical cohorts. Prevention and management of delirium for patients presenting with hip fracture, extending along a continuum from arrival through to the post-operative setting. Best practice guidelines emphasise multidisciplinary care including management by an orthogeriatric service, regular delirium screening, and multimodal interventions. The evidence base for prevention is strongest in terms of multifaceted interventions, while once delirium has set in, early recognition and identification of the cause are key. Integration of effective strategies is often suboptimal, and may be supported by approaches such as interactive teaching methodologies, routine feedback, and clear protocol dissemination. Partnering with patients and carers will support person centred care, improve patient experiences, and may improve outcomes. Ongoing work needs to focus on implementing recognised best practice, in order to minimise the health, social and economic costs of delirium.